UTILIZATION OF COCOYAM (Xanthosoma sp.) FLOUR FOR FOOD - Dizon-Lauzon, Roberta; Mabesa, Linda B. (Annals of Tropical Research, 1988)
Cocoyam flour was prepared into cookies, chips and noodles and used as binder in meat loaf. The sensory attributes of the products were comparable to the same products produced from wheat flour and corn starch, and all the processed products were acceptable. Product evaluation revealed that the level of cocoyam flour in meat loaf formulation is inversely related to the degree of shrinkage and volume of drippings. Cookie measurements showed that the height and weight of baked cookies were not significantly affected by the addition of cocoyam flour. However, the diameter and spread ratio of baked cookies decreased.